Vehicle Color-Type Detection Based on YOLOv8 and K-Means - Çiçek, İrem; Apaydın, Nafiye Nur; Kılıç, İrfan; Yaman, Orhan; Karaköse, Mehmet (Niyazi BULUT, 2026)
There is provided a computing device for managing honeybee colonies for pollination of crop(s), comprises: a processor(s) configured for: for each one of a plurality of honeybee colonies positioned for pollination of crop(s) in a geographical area: obtaining in-colony feature(s), computed based on output of internal sensor(s) monitoring the honeybee colony, wherein the in-colony feature(s) is indicative of an internal state of the honeybee colony positioned for pollination of crop(s) in the geographical area, obtaining out-colony feature(s), computed based on output of external sensor(s) monitoring the environment of the honeybee colony, wherein the out-colony feature is indicative of an external environment of the honeybee colony, feeding a combination of the in-colony feature(s) and the out-colony feature(s) into a machine learning model, and obtaining an outcome indicating pollination effectiveness of the honeybee colony.
Grant No: 5220154
Keywords: Vehicle color and type detections; Traffic Road Object Detection Dataset; YOLOv8; K-Means